Pengaruh Pemberian Getuk Ubi Jalar Ungu (Ipomea Batatas L) terhadap Pengendalian Glukosa Darah pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Sei Langkai - Rani Wahyuningsih; Haqqelni Nur Rosyidah; Amalina Rizma (Pusat Riset dan Inovasi Nasional, 2026)
Diabetes Mellitus (DM) is a metabolic disorder characterized by high blood sugar levels due to impaired insulin secretion, which results in impaired metabolism of fats (lipids), proteins, and carbohydrates. (Yulyastuti et al., 2021). Purple sweet potato (Ipomoea batatas L.) has the carbohydrates contained in purple sweet potatoes are on the Low Glycamix Index, so consumption will not drastically increase blood glucose. This study used a quasi-experimental method with a One Group Pretest-Posttest Design and serves to examine the impact of giving purple sweet potato getuk on blood glucose control in Type 2 Diabetes Mellitus patients. The sample size was 15 people and was selected using a purposive sampling technique. Data collection included data on age, gender, and blood glucose levels before and after the intervention. Data analysis used a Paired T-Test. The results showed that respondents' blood glucose levels increased from an average of 95.67 ± 4.73 mg / dL (pre-test) to 100.33 ± 3.26 mg / dL (post-test). The effect of purple sweet potato getuk on controlling blood glucose in patients with Type 2 Diabetes Mellitus was obtained from the results of the p-value = 0.001 (<0.05). In conclusion, blood glucose levels before the intervention were different from those after the intervention (p = 0.001), which means that the administration of purple sweet potato getuk had an effect on controlling blood glucose levels in Type 2 Diabetes Mellitus patients.